2021
DOI: 10.3390/polym13203540
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Soybean Protein Concentrate Adhesive as Binder of Rice Husk Particleboards

Abstract: The aim of this research was to prepare an antifungal soybean protein concentrate (SPC) adhesive containing carvacrol (CRV) as a bioactive agent able to delay the attack of molds and yeast during storage of SPC adhesive at 4 °C as water-based systems. CRV was incorporated in SPC slurry at 0.5% v/v (~10 times its minimum inhibitory concentration against Aspergillus terreus, used as model fungus), to ensure its long-term action. CRV scarcely altered the thermal properties, structure and apparent viscosity of SPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The processing conditions for the BSG particleboards were chosen based on our prior studies involving other substrates [ 12 , 28 ] and preliminary trials. Regardless of the applied pressing temperature, the pressure and pressing time for the binderless boards were maintained at 2.1 MPa and 15 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The processing conditions for the BSG particleboards were chosen based on our prior studies involving other substrates [ 12 , 28 ] and preliminary trials. Regardless of the applied pressing temperature, the pressure and pressing time for the binderless boards were maintained at 2.1 MPa and 15 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although PAB boards exhibited significantly improved mechanical properties compared to those without a binder, the mechanical results observed in the obtained boards were even lower than those achieved using other substrates such as wood [ 81 ] or rice husk [ 12 ] combined with synthetic adhesive. The low MOE values of BSG boards might be related to their low cellulose content (9.5%), compared to, for example, eucalyptus wood (approximately 40%) and other lignocellulosic wastes like rice husk (30%) [ 12 , 24 , 27 , 28 ]. A similar reduction in MOE values was also observed by Barbu [ 13 ] when substituting spruce wood with BSG in particleboard using different synthetic adhesives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension formed by A. niger and spores was collected and transferred to a sterile tube. The optical density (OD) of the suspension was adjusted to 0.05 using a UV–visible spectrophotometer at 600 nm, adapted by Su et al and Larregle et al [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study showed that the bending strength and internal bond strength of particleboards produced with the use of PVAc glue are lower than for panels produced with the use of UF resin [ 9 ]. In recent years, a considerable amount of research has been done on natural adhesives from sustainable resources such as lignin [ 10 , 11 , 12 ], soybean [ 12 , 13 , 14 ], condensed tannins [ 15 , 16 , 17 , 18 ], and suberinic acids [ 19 ] in the partial of full replacement of PF. Condensed tannins (CTs) from lignocellulosic biomass could potentially be eco-friendly substitutes for phenol in adhesives due to the high reactivity of CTs toward aldehydes, including formaldehyde [ 20 ].…”
Section: Introductionmentioning
confidence: 99%